ANALISIS RESIKO MSDs (MUSCULOSKELETAL DISORDERS) TERHADAP POSTUR KERJA KARYAWAN BAGIAN SANDING DENGAN METODE NBM DAN RULA (Science and Technology (SciTech), 2023)
Musculoskeletal Disorders (MSDs) are disorders or injuries to the muscles, bones, joint and the same like. Which is caused by several factors such as work position, unhealthy lifestyle, repetitive and continous activities, trauma and so on. At Cv. Jati Home Indonesia found complaints of pain felt by partner employees and is thougt to be an indication of the arms, legs. And the problem is the result of the pain complaint can hinder work activities. Therefore it is necessary to have further analysis of these problems in order to obtain clarity and solutions. There are 2 methods used, namely the Nordic Body Map (NBM) questionnaire to analyze pain complaints. And then the Rapid Upper Limb Asessment ( RULA) method is used to analyze the work posture of the counterpart employees. By knowing the result of the total score of tje NBM questionnaire it can be used as a first step to wheter improvement is needed or not. Whereas the result of tej RULA assesment ae used as how much influence the employee’s work posture has on the occurrence of pain complaints. And the results of the two are expected to be a reference for improvement solutions.